Does Governance Matter? Keiretsu Alliances and Asset Specificity as Sources of Japanese Competitive Advantage - Dyer, Jeffrey H. (Organization Science, 1996)
This empirical study suggests that Japanese competitive advantage in complex-product industries is at least partly due to differences in value chain governance and interfirm asset co-specialization. Comparative data are offered which indicate that U.S. firms rely largely on markets and hierarchies to facilitate exchange, whereas Japanese firms rely largely on “hybrid” governance or alliances. The empirical findings suggest that Japanese automotive firms (value chains) have been able to achieve a competitive advantage over their U.S. counterparts by effectively using hybrid/alliance governance for three primary reasons: (1) Japanese automotive value chains are characterized by greater interfirm asset co-specialization than U.S. chains. In particular, greater human asset co-specialization between firms results in superior coordination, information sharing, and learning which is critical in complex-product industries, (2) hybrids/alliances as employed by Japanese automakers realize virtually all of the advantages of hierarchy (e.g., asset co-specialization) without the disadvantages (e.g., loss of market discipline, loss of flexibility, higher labor costs), and (3) Japanese automotive value chains incur lower transaction costs than U.S. value chains. Thus, alliances, as structured in Japan, simultaneously realize the benefits of decentralization and competition without sacrificing economies of scale, coordination, or co-specialization of assets. These findings support transaction cost theories which suggest that effectively aligning governance structures with transactions will result in efficiency advantages. However, inconsistent with extant transaction cost theory, findings from this study suggest that: (1) hybrid governance may be more efficient than hierarchical governance under conditions of uncertainty, and (2) transaction costs do not necessarily increase with an increase in asset specificity.